Peroxisome Proliferator-Activated Receptors as a Therapeutic Target in Asthma - Oxana Yu. Kytikova; Juliy M. Perelman; Tatyana P. Novgorodtseva; Yulia K. Denisenko; Viktor P. Kolosov; Marina V. Antonyuk; Tatyana A. Gvozdenko (PPAR Research)
The complexity of the pathogenetic mechanisms of the development of chronic inflammation in asthma determines its heterogeneity and insufficient treatment effectiveness. Nuclear transcription factors, which include peroxisome proliferator-activated receptors, that is, PPARs, play an important role in the regulation of initiation and resolution of the inflammatory process. The ability of PPARs to modulate not only lipid homeostasis but also the activity of the inflammatory response makes them an important pathogenetic target in asthma therapy. At present, special attention is focused on natural (polyunsaturated fatty acids (PUFAs), endocannabinoids, and eicosanoids) and synthetic (fibrates, thiazolidinediones) PPAR ligands and the study of signaling mechanisms involved in the implementation of their anti-inflammatory effects in asthma. This review summarizes current views on the structure and function of PPARs, as well as their participation in the pathogenesis of chronic inflammation in asthma. The potential use of PPAR ligands as therapeutic agents for treating asthma is under discussion.